Preparation method of soil curing capsule based on recycled aggregate and calcium salt inner core

Through the preparation method of soil cured capsules based on regenerated aggregate and calcium salt inner core, the problems of high energy consumption and environmental pollution of traditional curing agents are solved, efficient soil curing is achieved, and the overall strength and stability of soil are improved. , suitable for a variety of engineering applications.

CN119120032AInactive Publication Date: 2024-12-13HENAN INST OF ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411247298.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional soil curing agents such as cement and lime have problems of high energy consumption and environmental pollution during use, and it is difficult to effectively improve the overall strength and stability of the soil.

Method used

The preparation method of soil-cured capsules based on regenerated aggregate and calcium salt inner core is used to react calcium ions with moisture and clay minerals in the soil to generate calcium silicate and calcium aluminate, combining polyacrylamide and polyethylene. Alcohol forms a polymer network structure, and chlorophoric acid is added to reduce porosity and form a solid overall structure.

Benefits of technology

This method reduces resource consumption and environmental pollution, improves the compressive degree and stability of the soil, enhances the overall strength and shear strength of the soil, and is suitable for road construction and stabilization treatment of polluted soil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005031152770000101
    Figure BDA0005031152770000101
Patent Text Reader

Abstract

The invention provides a preparation method of a soil body curing capsule based on recycled aggregate and a calcium salt inner core, relates to the field of soil body curing, and provides the preparation method of the soil body curing capsule based on the recycled aggregate and the calcium salt inner core. Comprising the following steps: obtaining the following components in parts by weight: 50-60 parts of recycled aggregate, 10-15 parts of calcium chloride, 12-18 parts of calcium sulfate, 8-10 parts of polyacrylamide, 12-16 parts of polyvinyl alcohol, 3-5 parts of fulvic acid, 5-8 parts of reinforced fibers and 70-80 parts of water; the preparation method comprises the following steps: coating the outer surface of an inner core mixture containing calcium chloride and calcium sulfate with a coating solution containing a polyacrylamide solution and polyvinyl alcohol to obtain the soil curing capsule based on the recycled aggregate and the calcium salt inner core. Resource consumption and environmental pollution are reduced, and the compressive strength of soil solidification is improved by adding polyacrylamide and polyvinyl alcohol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of soil solidification, and in particular to a method for preparing a soil solidification capsule based on recycled aggregate and a calcium salt inner core. Background Art

[0002] Soil stabilization is a method of improving the engineering properties of soil by physical or chemical means to meet the needs of specific projects. Soil stabilization technology is widely used in road construction, foundation reinforcement, slope stabilization and other fields.

[0003] The solidified soil has the following advantages:

[0004] 1. The solidified soil has a higher bearing capacity and can withstand greater loads without excessive deformation;

[0005] 2. Solidification treatment can significantly reduce the compressibility of soil and reduce the reduction of soil volume under load;

[0006] 3. The stability of the solidified soil is enhanced and it can resist the impact of natural disasters such as erosion, sliding and liquefaction. The solidification process can change the permeability of the soil and reduce the penetration of water, thereby reducing the impact of groundwater level changes on soil stability;

[0007] 4. Solidification treatment helps to reduce uneven settlement of soil during construction and use. The shear strength of solidified soil is improved, which is beneficial to resist shear force and enhance the stability of slopes and foundations.

[0008] 5. Solidification technology can be used to treat contaminated soil. Through solidification and stabilization technology, harmful substances in the soil can be reduced, thereby reducing the risk of environmental pollution.

[0009] When solidifying the soil, a solidifying agent is needed. Traditional solidifying agents such as cement and lime have certain solidifying effects when using cement and lime to solidify the soil, but there are problems of high energy consumption and environmental pollution.

[0010] Therefore, it is necessary to provide a new method for preparing soil solidification capsules based on recycled aggregate and calcium salt core to solve the above technical problems. Summary of the invention

[0011] In order to solve the above technical problems, the present invention provides a method for preparing soil solidification capsules based on recycled aggregate and a calcium salt inner core.

[0012] The method for preparing a soil solidification capsule based on recycled aggregate and a calcium salt inner core provided by the present invention comprises the following steps:

[0013] S1: Obtain the following components in parts by weight: 50-60 parts of recycled aggregate, 10-15 parts of calcium chloride, 12-18 parts of calcium sulfate, 1-2 parts of polyacrylamide, 1-2 parts of polyvinyl alcohol, 3-5 parts of fulvic acid, 5-8 parts of reinforcing fiber, and 30-40 parts of water;

[0014] S2: Add calcium chloride, calcium sulfate and water into a container and stir for 10-15 minutes to obtain a calcium salt solution;

[0015] S3: Heat the calcium salt solution to 50-60°C, stir for 5 minutes, add the recycled aggregate, stir for 30-60 minutes, stir evenly, and then keep it at a constant temperature of 50°C for 3-6 hours to allow the calcium salt solution to penetrate into the recycled aggregate to obtain the inner core mixture;

[0016] S4: Add water to the container and heat it to 30-35° C., add polyacrylamide to the water while stirring, and after the polyacrylamide is completely added, heat it to 40-45° C. to obtain a polyacrylamide solution;

[0017] S5: Add water to the container, heat to 40-50° C., add polyvinyl alcohol to the water, heat to 50-55° C., and stir evenly to obtain a polyvinyl alcohol solution;

[0018] S6: Mix the polyacrylamide solution and the polyvinyl alcohol solution, stir for 20-35 minutes, heat to 65-70°C, add fulvic acid and reinforcing fiber, stir for 45-55 minutes, mix all the substances evenly, and obtain a coating solution;

[0019] S7: adding the inner core mixture to the coating solution, stirring while adding, so that the coating solution is coated on the outer surface of the inner core mixture, processing into a capsule-shaped substance, and drying the capsule-shaped substance to obtain a finished product.

[0020] Preferably, in the step S6, after adding fulvic acid and reinforcing fiber, the stirring is performed in a clockwise and counterclockwise intermittent manner, and the stirring process is controlled to stir clockwise for 1-3 minutes and then stir counterclockwise for 1-3 minutes, wherein the rotation speed during clockwise stirring is 300 rpm, and the rotation speed during counterclockwise stirring is 500 rpm.

[0021] Preferably, the reinforcing fibers include glass fibers and auxiliary fibers, wherein the weight ratio of the glass fibers to the auxiliary fibers is 2:1.

[0022] Preferably, the auxiliary fiber is any one of carbon fiber, polyester fiber, polypropylene fiber and coconut shell fiber.

[0023] Preferably, the glass fiber is any one of chopped glass fiber and continuous glass fiber.

[0024] Preferably, the recycled aggregate includes recycled fine aggregate and recycled coarse aggregate, wherein the weight ratio of the recycled fine aggregate to the recycled coarse aggregate is 2:3.

[0025] Preferably, the particle size of the recycled fine aggregate is 0.5-5 mm, and the particle size of the recycled coarse aggregate is 7-20 mm.

[0026] Preferably, the preparation of the recycled aggregate comprises the following steps:

[0027] The construction solid waste is crushed, and after the crushing is completed, the aggregates with different particle sizes are screened out, and the screened aggregates are cleaned to remove the soil and sand impurities on the surface of the aggregates to obtain recycled aggregates.

[0028] Compared with the related art, the method for preparing soil solidification capsules based on recycled aggregate and calcium salt inner core provided by the present invention has the following beneficial effects:

[0029] 1. The present invention uses recycled aggregate, calcium chloride and calcium sulfate when solidifying the soil. Calcium ions react with moisture and clay minerals in the soil. Calcium ions can react with silicates to generate hydrated calcium silicate, and calcium ions can also react with aluminates to generate hydrated calcium aluminate. The generated substances can cement soil particles together to form a solid overall structure. At the same time, the recycled aggregate serves as a skeleton material to further improve the overall strength and stability of the solidified soil.

[0030] 2. The present invention mainly solidifies the soil through recycled aggregate, calcium chloride and calcium sulfate. Compared with the traditional solidification method of cement and lime, it reduces resource consumption and environmental pollution and has certain environmental protection.

[0031] 3. The present invention adds polyacrylamide and polyvinyl alcohol during soil solidification. The high molecular weight on the polyacrylamide molecular chain reacts with the soil surface to form a polymer network structure, thereby tightly bonding the soil particles together and improving the soil's compressive strength and stability. In addition, polyvinyl alcohol can be mixed with water to form a gel-like substance, which can combine with the soil to improve soil strength.

[0032] 4. The present invention adds fulvic acid during soil solidification. Since fulvic acid has more carboxyl groups and phenolic hydroxyl groups, these functional groups react with metal ions in the soil to form a complex or chelate reaction, thereby reducing soil porosity and improving soil compactness. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with the embodiments.

[0034] In the specific implementation process,

[0035] Embodiment 1

[0036] The following steps are involved:

[0037] S1: Obtain the following components by weight: 50 parts of recycled aggregate, 10 parts of calcium chloride, 12 parts of calcium sulfate, 8 parts of polyacrylamide, 12 parts of polyvinyl alcohol, 3 parts of fulvic acid, 5 parts of reinforcing fiber, and 70 parts of water;

[0038] The preparation of recycled aggregate includes the following steps: crushing construction solid waste, screening out aggregates with different particle sizes after crushing, washing the screened aggregates, removing soil and sand impurities on the surface of the aggregates, and obtaining recycled aggregates, wherein the recycled aggregates include recycled fine aggregates and recycled coarse aggregates, wherein the weight ratio of the recycled fine aggregates to the recycled coarse aggregates is 2:3, the particle size of the recycled fine aggregates is 0.5-5mm, and the particle size of the recycled coarse aggregates is 7-20mm, and the reinforcing fibers include glass fibers and auxiliary fibers, wherein the weight ratio of the glass fibers to the auxiliary fibers is 2:1, and the weight ratio of the glass fibers to the auxiliary fibers is 2:1, and the auxiliary fibers are any one of carbon fibers, polyester fibers, polypropylene fibers and coconut shell fibers, and the glass fibers are any one of chopped glass fibers and continuous glass fibers;

[0039] S2: Add calcium chloride, calcium sulfate and water into a container and stir for 10-15 minutes to obtain a calcium salt solution;

[0040] S3: Heat the calcium salt solution to 50-60°C, stir for 5 minutes, add the recycled aggregate, stir for 30-60 minutes, stir evenly, and then keep it at a constant temperature of 50°C for 3-6 hours to allow the calcium salt solution to penetrate into the recycled aggregate to obtain the inner core mixture;

[0041] S4: Add water to the container and heat it to 30-35° C., add polyacrylamide to the water while stirring, and after the polyacrylamide is completely added, heat it to 40-45° C. to obtain a polyacrylamide solution;

[0042] S5: Add water to the container, heat to 40-50° C., add polyvinyl alcohol to the water, heat to 50-55° C., and stir evenly to obtain a polyvinyl alcohol solution;

[0043] S6: Mix the polyacrylamide solution and the polyvinyl alcohol solution, stir for 20-35 minutes, heat to 65-70°C, add fulvic acid and reinforcing fiber, stir for 45-55 minutes, mix the various substances evenly, and obtain a coating solution. After adding fulvic acid and reinforcing fiber, stir them in a clockwise and counterclockwise intermittent manner. The stirring process is controlled to stir clockwise for 1-3 minutes and then stir counterclockwise for 1-3 minutes. The rotation speed during clockwise stirring is 300 rpm, and the rotation speed during counterclockwise stirring is 500 rpm.

[0044] S7: adding the inner core mixture to the coating solution while stirring, so that the coating solution is coated on the outer surface of the inner core mixture, processing it into a capsule-shaped substance by extrusion molding, and drying the capsule-shaped substance to obtain a finished product.

[0045] Embodiment 2

[0046] The following steps are involved:

[0047] S1: Obtain the following components by weight: 55 parts of recycled aggregate, 12.5 parts of calcium chloride, 15 parts of calcium sulfate, 9 parts of polyacrylamide, 14 parts of polyvinyl alcohol, 4 parts of fulvic acid, 6.5 parts of reinforcing fiber, and 75 parts of water;

[0048] The preparation of recycled aggregate includes the following steps: crushing construction solid waste, screening out aggregates with different particle sizes after crushing, washing the screened aggregates, removing soil and sand impurities on the surface of the aggregates, and obtaining recycled aggregates, wherein the recycled aggregates include recycled fine aggregates and recycled coarse aggregates, wherein the weight ratio of the recycled fine aggregates to the recycled coarse aggregates is 2:3, the particle size of the recycled fine aggregates is 0.5-5mm, and the particle size of the recycled coarse aggregates is 7-20mm, and the reinforcing fibers include glass fibers and auxiliary fibers, wherein the weight ratio of the glass fibers to the auxiliary fibers is 2:1, and the weight ratio of the glass fibers to the auxiliary fibers is 2:1, and the auxiliary fibers are any one of carbon fibers, polyester fibers, polypropylene fibers and coconut shell fibers, and the glass fibers are any one of chopped glass fibers and continuous glass fibers;

[0049] S2: Add calcium chloride, calcium sulfate and water into a container and stir for 10-15 minutes to obtain a calcium salt solution;

[0050] S3: Heat the calcium salt solution to 50-60°C, stir for 5 minutes, add the recycled aggregate, stir for 30-60 minutes, stir evenly, and then keep it at a constant temperature of 50°C for 3-6 hours to allow the calcium salt solution to penetrate into the recycled aggregate to obtain the inner core mixture;

[0051] S4: Add water to the container and heat it to 30-35° C., add polyacrylamide to the water while stirring, and after the polyacrylamide is completely added, heat it to 40-45° C. to obtain a polyacrylamide solution;

[0052] S5: Add water to the container, heat to 40-50° C., add polyvinyl alcohol to the water, heat to 50-55° C., and stir evenly to obtain a polyvinyl alcohol solution;

[0053] S6: Mix the polyacrylamide solution and the polyvinyl alcohol solution, stir for 20-35 minutes, heat to 65-70°C, add fulvic acid and reinforcing fiber, stir for 45-55 minutes, mix the various substances evenly, and obtain a coating solution. After adding fulvic acid and reinforcing fiber, stir them in a clockwise and counterclockwise intermittent manner. The stirring process is controlled to stir clockwise for 1-3 minutes and then stir counterclockwise for 1-3 minutes. The rotation speed during clockwise stirring is 300 rpm, and the rotation speed during counterclockwise stirring is 500 rpm.

[0054] S7: adding the inner core mixture to the coating solution while stirring, so that the coating solution is coated on the outer surface of the inner core mixture, processing it into a capsule-shaped substance by extrusion molding, and drying the capsule-shaped substance to obtain a finished product.

[0055] Embodiment 3

[0056] The following steps are involved:

[0057] S1: Obtain the following components in parts by weight: 60 parts of recycled aggregate, 15 parts of calcium chloride, 18 parts of calcium sulfate, 10 parts of polyacrylamide, 16 parts of polyvinyl alcohol, 5 parts of fulvic acid, 8 parts of reinforcing fiber, and 80 parts of water;

[0058] The preparation of recycled aggregate includes the following steps: crushing construction solid waste, screening out aggregates with different particle sizes after crushing, washing the screened aggregates, removing soil and sand impurities on the surface of the aggregates, and obtaining recycled aggregates, wherein the recycled aggregates include recycled fine aggregates and recycled coarse aggregates, wherein the weight ratio of the recycled fine aggregates to the recycled coarse aggregates is 2:3, the particle size of the recycled fine aggregates is 0.5-5mm, and the particle size of the recycled coarse aggregates is 7-20mm, and the reinforcing fibers include glass fibers and auxiliary fibers, wherein the weight ratio of the glass fibers to the auxiliary fibers is 2:1, and the weight ratio of the glass fibers to the auxiliary fibers is 2:1, and the auxiliary fibers are any one of carbon fibers, polyester fibers, polypropylene fibers and coconut shell fibers, and the glass fibers are any one of chopped glass fibers and continuous glass fibers;

[0059] S2: Add calcium chloride, calcium sulfate and water into a container and stir for 10-15 minutes to obtain a calcium salt solution;

[0060] S3: Heat the calcium salt solution to 50-60°C, stir for 5 minutes, add the recycled aggregate, stir for 30-60 minutes, stir evenly, and then keep it at a constant temperature of 50°C for 3-6 hours to allow the calcium salt solution to penetrate into the recycled aggregate to obtain the inner core mixture;

[0061] S4: Add water to the container and heat it to 30-35° C., add polyacrylamide to the water while stirring, and after the polyacrylamide is completely added, heat it to 40-45° C. to obtain a polyacrylamide solution;

[0062] S5: Add water to the container, heat to 40-50° C., add polyvinyl alcohol to the water, heat to 50-55° C., and stir evenly to obtain a polyvinyl alcohol solution;

[0063] S6: Mix the polyacrylamide solution and the polyvinyl alcohol solution, stir for 20-35 minutes, heat to 65-70°C, add fulvic acid and reinforcing fiber, stir for 45-55 minutes, mix the various substances evenly, and obtain a coating solution. After adding fulvic acid and reinforcing fiber, stir them in a clockwise and counterclockwise intermittent manner. The stirring process is controlled to stir clockwise for 1-3 minutes and then stir counterclockwise for 1-3 minutes. The rotation speed during clockwise stirring is 300 rpm, and the rotation speed during counterclockwise stirring is 500 rpm.

[0064] S7: adding the inner core mixture to the coating solution while stirring, so that the coating solution is coated on the outer surface of the inner core mixture, processing it into a capsule-shaped substance by extrusion molding, and drying the capsule-shaped substance to obtain a finished product.

[0065] Comparative Example 1

[0066] The following steps are involved:

[0067] S1: Obtain the following components by weight: 50 parts of recycled aggregate, 10 parts of calcium chloride, 12 parts of calcium sulfate, 12 parts of polyvinyl alcohol, 3 parts of fulvic acid, 5 parts of reinforcing fiber, and 70 parts of water;

[0068] The preparation of recycled aggregate includes the following steps: crushing construction solid waste, screening out aggregates with different particle sizes after crushing, washing the screened aggregates, removing soil and sand impurities on the surface of the aggregates, and obtaining recycled aggregates, wherein the recycled aggregates include recycled fine aggregates and recycled coarse aggregates, wherein the weight ratio of the recycled fine aggregates to the recycled coarse aggregates is 2:3, the particle size of the recycled fine aggregates is 0.5-5mm, and the particle size of the recycled coarse aggregates is 7-20mm, and the reinforcing fibers include glass fibers and auxiliary fibers, wherein the weight ratio of the glass fibers to the auxiliary fibers is 2:1, and the weight ratio of the glass fibers to the auxiliary fibers is 2:1, and the auxiliary fibers are any one of carbon fibers, polyester fibers, polypropylene fibers and coconut shell fibers, and the glass fibers are any one of chopped glass fibers and continuous glass fibers;

[0069] S2: Add calcium chloride, calcium sulfate and water into a container and stir for 10-15 minutes to obtain a calcium salt solution;

[0070] S3: Heat the calcium salt solution to 50-60°C, stir for 5 minutes, add the recycled aggregate, stir for 30-60 minutes, stir evenly, and then keep it at a constant temperature of 50°C for 3-6 hours to allow the calcium salt solution to penetrate into the recycled aggregate to obtain the inner core mixture;

[0071] S4: Add water to the container, heat to 40-50°C, add polyvinyl alcohol to the water, heat to 50-55°C, and stir evenly to obtain a polyvinyl alcohol solution;

[0072] S5: heating the polyvinyl alcohol solution to 65-70°C, adding fulvic acid and reinforcing fiber, stirring for 45-55 minutes to mix various substances evenly, and obtaining a coating solution. After adding fulvic acid and reinforcing fiber, stirring is performed in a clockwise and counterclockwise intermittent manner. The stirring process is controlled to stir clockwise for 1-3 minutes, and then stir counterclockwise for 1-3 minutes. The rotation speed during clockwise stirring is 300 rpm, and the rotation speed during counterclockwise stirring is 500 rpm.

[0073] S6: adding the inner core mixture to the coating solution while stirring, so that the coating solution is coated on the outer surface of the inner core mixture, processing it into a capsule-shaped substance by extrusion molding, and drying the capsule-shaped substance to obtain a finished product.

[0074] Comparative Example 2

[0075] The following steps are involved:

[0076] S1: Obtain the following components by weight: 50 parts of recycled aggregate, 10 parts of calcium chloride, 12 parts of calcium sulfate, 8 parts of polyacrylamide, 3 parts of fulvic acid, 5 parts of reinforcing fiber, and 70 parts of water;

[0077] The preparation of recycled aggregate includes the following steps: crushing construction solid waste, screening out aggregates with different particle sizes after crushing, washing the screened aggregates, removing soil and sand impurities on the surface of the aggregates, and obtaining recycled aggregates, wherein the recycled aggregates include recycled fine aggregates and recycled coarse aggregates, wherein the weight ratio of the recycled fine aggregates to the recycled coarse aggregates is 2:3, the particle size of the recycled fine aggregates is 0.5-5mm, and the particle size of the recycled coarse aggregates is 7-20mm, and the reinforcing fibers include glass fibers and auxiliary fibers, wherein the weight ratio of the glass fibers to the auxiliary fibers is 2:1, and the weight ratio of the glass fibers to the auxiliary fibers is 2:1, and the auxiliary fibers are any one of carbon fibers, polyester fibers, polypropylene fibers and coconut shell fibers, and the glass fibers are any one of chopped glass fibers and continuous glass fibers;

[0078] S2: Add calcium chloride, calcium sulfate and water into a container and stir for 10-15 minutes to obtain a calcium salt solution;

[0079] S3: Heat the calcium salt solution to 50-60°C, stir for 5 minutes, add the recycled aggregate, stir for 30-60 minutes, stir evenly, and then keep it at a constant temperature of 50°C for 3-6 hours to allow the calcium salt solution to penetrate into the recycled aggregate to obtain the inner core mixture;

[0080] S4: Add water to the container and heat it to 30-35° C., add polyacrylamide to the water while stirring, and after the polyacrylamide is completely added, heat it to 40-45° C. to obtain a polyacrylamide solution;

[0081] S5: heating the polyacrylamide solution to 65-70°C, adding fulvic acid and reinforcing fiber, stirring for 45-55 minutes to mix various substances evenly, and obtaining a coating solution. After adding fulvic acid and reinforcing fiber, stirring is performed in a clockwise and counterclockwise intermittent manner. The stirring process is controlled to stir clockwise for 1-3 minutes, and then stir counterclockwise for 1-3 minutes. The rotation speed during clockwise stirring is 300 rpm, and the rotation speed during counterclockwise stirring is 500 rpm.

[0082] S6: adding the inner core mixture to the coating solution while stirring, so that the coating solution is coated on the outer surface of the inner core mixture, processing it into a capsule-shaped substance by extrusion molding, and drying the capsule-shaped substance to obtain a finished product.

[0083] Comparative Example 3

[0084] The following steps are involved:

[0085] S1: Obtain the following components by weight: 50 parts of recycled aggregate, 10 parts of calcium chloride, 12 parts of calcium sulfate, 8 parts of polyacrylamide, 12 parts of polyvinyl alcohol, 5 parts of reinforcing fiber, and 70 parts of water;

[0086] The preparation of recycled aggregate includes the following steps: crushing construction solid waste, screening out aggregates with different particle sizes after crushing, washing the screened aggregates, removing soil and sand impurities on the surface of the aggregates, and obtaining recycled aggregates, wherein the recycled aggregates include recycled fine aggregates and recycled coarse aggregates, wherein the weight ratio of the recycled fine aggregates to the recycled coarse aggregates is 2:3, the particle size of the recycled fine aggregates is 0.5-5mm, and the particle size of the recycled coarse aggregates is 7-20mm, and the reinforcing fibers include glass fibers and auxiliary fibers, wherein the weight ratio of the glass fibers to the auxiliary fibers is 2:1, and the weight ratio of the glass fibers to the auxiliary fibers is 2:1, and the auxiliary fibers are any one of carbon fibers, polyester fibers, polypropylene fibers and coconut shell fibers, and the glass fibers are any one of chopped glass fibers and continuous glass fibers;

[0087] S2: Add calcium chloride, calcium sulfate and water into a container and stir for 10-15 minutes to obtain a calcium salt solution;

[0088] S3: Heat the calcium salt solution to 50-60°C, stir for 5 minutes, add the recycled aggregate, stir for 30-60 minutes, stir evenly, and then keep it at a constant temperature of 50°C for 3-6 hours to allow the calcium salt solution to penetrate into the recycled aggregate to obtain the inner core mixture;

[0089] S4: Add water to the container and heat it to 30-35° C., add polyacrylamide to the water while stirring, and after the polyacrylamide is completely added, heat it to 40-45° C. to obtain a polyacrylamide solution;

[0090] S5: Add water to the container, heat to 40-50° C., add polyvinyl alcohol to the water, heat to 50-55° C., and stir evenly to obtain a polyvinyl alcohol solution;

[0091] S6: Mix the polyacrylamide solution and the polyvinyl alcohol solution, stir for 20-35 minutes, heat to 65-70°C, add the reinforcing fiber, stir for 45-55 minutes, mix the various substances evenly, and obtain a coating solution. After adding the reinforcing fiber, stir the solution in a clockwise and counterclockwise intermittent manner. The stirring process is controlled to stir clockwise for 1-3 minutes and then stir counterclockwise for 1-3 minutes. The rotation speed during clockwise stirring is 300 rpm, and the rotation speed during counterclockwise stirring is 500 rpm.

[0092] S7: adding the inner core mixture to the coating solution while stirring, so that the coating solution is coated on the outer surface of the inner core mixture, processing it into a capsule-shaped substance by extrusion molding, and drying the capsule-shaped substance to obtain a finished product.

[0093] Experimental Group:

[0094] The finished products obtained in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were mixed with water at a mass ratio of 7:2 to obtain a mixture, and the mixture was added to the soil to be solidified at a mass fraction of 0.025%, and the mixture and the soil were stirred evenly, and the curing method in JTGE51-2009 "Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering" was used for curing. Unconfined compressive strength tests were performed 3 days, 7 days, 11 days, and 15 days after curing, respectively. The compressive strength (MPa) obtained from the test results is recorded as follows:

[0095]

[0096] It can be seen from the data in the table that the finished products prepared in each embodiment and the comparative example have an increasing compressive strength after curing for 3 days, 7 days, 11 days and 15 days. After curing for 3 days and 7 days, the compressive strength of the soil curing in Example 3 is lower than that of the soil curing in Example 1 and Example 2 after curing for 3 days and 7 days. However, as the curing time increases, the compressive strength of the soil curing in Example 3 shows a faster growth trend. After curing for 11 days and 15 days, the compressive strength of the soil curing in Example 3 is lower than that of the soil curing in Example 1 and Example 2 after curing for 3 days and 7 days. The compressive strength of the soil solidification in Example 3 is significantly higher than the compressive strength of the soil solidification in Example 1 and Example 2 after 11 days of curing and 15 days of curing. By comparing multiple embodiments and multiple comparative examples, it can be seen that at 3 days, 7 days, 11 days and 15 days after curing, the effect of Example 1 is stronger than that of the comparative example. By comparing Example 1 with Comparative Example 1, Example 1 with Comparative Example 2, and Example 1 with Comparative Example 3, it can be seen that the added polyacrylamide, polyvinyl alcohol and humic acid can enhance the compressive strength of soil solidification.

[0097] The circuits and controls involved in the present invention are all prior art and will not be described in detail here. The above description is only an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the present invention specification, or directly or indirectly applied in other related technical fields, is also included in the patent protection scope of the present invention.

Claims

1. A method for preparing soil solidification capsules based on recycled aggregate and calcium salt inner core, characterized in that: The following steps are involved: S1: Obtain the following components in parts by weight: 50-60 parts of recycled aggregate, 10-15 parts of calcium chloride, 12-18 parts of calcium sulfate, 8-10 parts of polyacrylamide, 12-16 parts of polyvinyl alcohol, 3-5 parts of fulvic acid, 5-8 parts of reinforcing fiber, and 70-80 parts of water; S2: Add calcium chloride, calcium sulfate and water into a container and stir for 10-15 minutes to obtain a calcium salt solution; S3: Heat the calcium salt solution to 50-60°C, stir for 5 minutes, add the recycled aggregate, stir for 30-60 minutes, stir evenly, and then keep it at a constant temperature of 50°C for 3-6 hours to allow the calcium salt solution to penetrate into the recycled aggregate to obtain the inner core mixture; S4: Add water to the container and heat it to 30-35° C., add polyacrylamide to the water while stirring, and after the polyacrylamide is completely added, heat it to 40-45° C. to obtain a polyacrylamide solution; S5: Add water to the container, heat to 40-50° C., add polyvinyl alcohol to the water, heat to 50-55° C., and stir evenly to obtain a polyvinyl alcohol solution; S6: Mix the polyacrylamide solution and the polyvinyl alcohol solution, stir for 20-35 minutes, heat to 65-70°C, add fulvic acid and reinforcing fiber, stir for 45-55 minutes, mix all the substances evenly, and obtain a coating solution; S7: adding the inner core mixture to the coating solution, stirring while adding, so that the coating solution is coated on the outer surface of the inner core mixture, processing into a capsule-shaped substance, and drying the capsule-shaped substance to obtain a finished product.

2. The method for preparing soil solidification capsules based on recycled aggregate and calcium salt inner core according to claim 1, characterized in that: In the step S6, after adding fulvic acid and reinforcing fiber, the stirring is performed in a clockwise and counterclockwise intermittent manner, and the stirring process is controlled to stir clockwise for 1-3 minutes and then stir counterclockwise for 1-3 minutes, wherein the rotation speed during clockwise stirring is 300 rpm and the rotation speed during counterclockwise stirring is 500 rpm.

3. The method for preparing soil solidification capsules based on recycled aggregate and calcium salt inner core according to claim 1, characterized in that: The reinforcing fibers include glass fibers and auxiliary fibers, wherein the weight ratio of the glass fibers to the auxiliary fibers is 2:

1.

4. The method for preparing soil solidification capsules based on recycled aggregate and calcium salt inner core according to claim 3, characterized in that: The auxiliary fiber is any one of carbon fiber, polyester fiber, polypropylene fiber and coconut shell fiber.

5. The method for preparing soil solidification capsules based on recycled aggregate and calcium salt inner core according to claim 3, characterized in that: The glass fiber is any one of chopped glass fiber and continuous glass fiber.

6. The method for preparing soil solidification capsules based on recycled aggregate and calcium salt inner core according to claim 1, characterized in that: The recycled aggregate includes recycled fine aggregate and recycled coarse aggregate, wherein the weight ratio of the recycled fine aggregate to the recycled coarse aggregate is 2:

3.

7. The method for preparing soil solidification capsules based on recycled aggregate and calcium salt inner core according to claim 6, characterized in that: The particle size of the recycled fine aggregate is 0.5-5 mm, and the particle size of the recycled coarse aggregate is 7-20 mm.

8. The method for preparing soil solidification capsules based on recycled aggregate and calcium salt inner core according to claim 7, characterized in that: The preparation of the recycled aggregate comprises the following steps: The construction solid waste is crushed, and after the crushing is completed, the aggregates with different particle sizes are screened out, and the screened aggregates are cleaned to remove the soil and sand impurities on the surface of the aggregates to obtain recycled aggregates.